A randomized controlled trial on long‐term effectiveness of a psychosocial aftercare program following paediatric chronic pain treatment: Who benefits the most?. (6th July 2022) - Dogan, Meltem; Hirschfeld, Gerrit; Blankenburg, Markus; Frühwald, Michael; Ahnert, Rosemarie; Braun, Sarah; Marschall, Ursula; Zernikow, Boris; Wager, Julia
Abstract: Background: For paediatric chronic pain patients, intensive interdisciplinary pain treatment (IIPT) is a well‐established treatment. The treatment's short‐term effectiveness can be improved by an additive psychosocial aftercare (PAC). However, neither the program's long‐term effectiveness nor the patients in particular need have been investigated yet. Methods: This study aimed at determining the long‐term effects of PAC and detecting predictors of treatment outcome within a multicentre randomized controlled trial measured at five time points up to 12 months after discharge. At inpatient admission to IIPT, patients ( N  = 419, 14.3 years of age, 72.3% female) were randomly assigned to intervention or control group. After IIPT discharge, the intervention group received PAC, whereas the control group received treatment as usual (TAU). Patient‐reported outcomes included pain and emotional characteristics. Clinicians assessed potential psychosocial risk factors and their prognosis of treatment outcome. Statistical analyses included mixed‐models and univariable logistic regressions. Results: Data at the 12‐month follow‐up ( n  = 288) showed a significant benefit of PAC compared with TAU; the majority (59.0%) of patients in the PAC‐group reported no chronic pain compared to 29.2% of TAU‐patients ( p  < 0.001). Patients with a single parent specifically benefited from PAC compared to TAU. Clinicians were able to make a reliable prognosis of treatment outcome, but did not successfully predict which patients would benefit the most from PAC. Conclusions: Study results suggest that PAC is highly effective irrespective of patient characteristics, but particularly for patients with single parents. Its broad implementation could help to improve the long‐term outcomes of youth with severely disabling chronic pain. Significance: A psychosocial aftercare following paediatric IIPT leads to significantly better pain and emotional outcomes compared to treatment as usual up to 12 months after discharge, especially for patients with single parents.